(untitled) (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted at the Hill Agricultural Research Station, Khagrachari from September 2002 to February 2003 to find out the effect of mulching method (Mulching one month before planting, mulching just after planting and no mulching) and planting times (01 October, 16 October and 01 November) on the yield and yield attributes of tomato in hill slope. The highest yield (21.43 t/ha) was obtained from plant where mulch was given one month before planting. Among three planting times, the highest yield (15.27 t/ha) was obtained from 01 October planting. In case of combined effect, mulching one month before planting with 01 October planting produced the highest yield (28.06 t/ha) of tomato in hill slope. Key Words: Mulching; planting time; tomato yield; hill slope. DOI: 10.3329/bjar.v34i2.5793 Bangladesh J. Agril. Res. 34(2): 227-232, June 2009